2013
DOI: 10.1111/eve.12092
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and resolution of zilpaterol hydrochloride toxicity in aQuarterHorse gelding

Abstract: Summary Zilpaterol hydrochloride is a β‐2 agonist utilised as a repartitioning agent in cattle. In recent years, it has also been used illicitly among human athletes and body builders, and administered to racehorses. While there are numerous anecdotal reports of the effects of zilpaterol in horses, this is the first documented clinical case of equine zilpaterol toxicity. The horse presented with marked tachycardia, profuse sweating and generalised muscle fasciculations. Ultimately, treatment was initiated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Adverse effects in horses after the administration of zilpaterol are reported by Wagner et al. () and Hepworth‐Warren and Alcott (). Wagner et al.…”
Section: Animal Health and Welfare Aspects Of The Use Of Zilpaterolmentioning
confidence: 79%
See 2 more Smart Citations
“…Adverse effects in horses after the administration of zilpaterol are reported by Wagner et al. () and Hepworth‐Warren and Alcott (). Wagner et al.…”
Section: Animal Health and Welfare Aspects Of The Use Of Zilpaterolmentioning
confidence: 79%
“…AST, CK, lactate dehydrogenase). Lameness and reluctance to ambulate was also observed after 2–3 days (Hepworth‐Warren and Alcott, ). When stopping the zilpaterol administration, horses returned to a clinically normal state after 2–4 weeks.…”
Section: Animal Health and Welfare Aspects Of The Use Of Zilpaterolmentioning
confidence: 99%
See 1 more Smart Citation
“…The case report in this issue by Hepworth‐Warren and Alcott is a well‐documented case of zilpaterol intoxication in horses. I congratulate the authors (Hepworth‐Warren and Alcott ) for this effort. The case as a record of chemical toxicity is complete and of great interest.…”
mentioning
confidence: 99%
“…This was an accidental overdose (Hepworth‐Warren and Alcott ). Interestingly, a historical comment indicated that the horse had received chronic monensin feeding ‘without harm’ according to the owner.…”
mentioning
confidence: 99%